MicroRNA-543 acts as a prognostic marker and promotes the cell proliferation in cervical cancer by BRCA1-interacting protein 1 - Huimin Dang; Pengsheng Zheng; Yu Liu; Xiaoling Wu; Xili Wu (Tumor Biology, 2017)
Human cervical cancer is one of the most common malignancies worldwide. Recent studies have focused on microRNAs that play crucial roles in cancer development and progression of cervical cancer. In this study, we aimed to analyse the biological function of microRNA-543 in cervical cancer. Samples of human cervical cancer and matched adjacent normal cervical tissues were collected, and expression level of microRNA-543 and the clinical characteristics of cervical cancer were investigated. We found that microRNA-543 expression was significantly elevated in cervical cancer and its aberrant expression levels were positively correlated with tumour size ( p  = 0.0315), differentiation ( p  = 0.0134), clinical stage ( p  = 0.0315) and overall ( p  = 0.0426) and disease-free survival ( p  = 0.0396) of cervical cancer. Overexpression of microRNA-543 in cancer-derived HeLa and SiHa facilitated cell growth and suppressed cell apoptosis, while down-regulation of microRNA-543 exerted a reverse effect on cell growth and apoptosis. In addition, we demonstrated that BRCA1-interacting protein 1 was directly regulated by microRNA-543 and the restoration of BRCA1-interacting protein 1 expression reversed the effects of microRNA-543 on cell proliferation. Taken together, these findings collectively demonstrate that microRNA-543 exerts its oncogene function by directly targeting BRCA1-interacting protein 1 in cervical cancer, indicating a potential novel potential prognostic biomarker and therapeutic target for cervical cancer.